Plant elicitor peptide induces endocytosis of plasma membrane proteins in Arabidopsis - Jing, Yanping; Zheng, Xiaojiang; Sharifi, Rouhallah; Chen, Jian (Frontiers in Plant Science, 2023)
In plants, the regulation of plasma membrane (PM) dynamics through endocytosis plays a crucial role in responding to external environmental cues and defending against pathogens. The Arabidopsis plant elicitor peptides (Peps), originating from precursor proteins called PROPEPs, have been implicated in various aspects of plant immunity. This study delves into the signaling pathway of Peps, particularly Pep1, and its effect on PM protein internalization. Using PIN2 and BRI1 as PM markers, we demonstrated that Pep1 stimulates the endocytosis of these PM-localized proteins through clathrin-mediated endocytosis (CME). CLC2 and CLC3, two light chains of clathrin, are vital for Pep1-induced PIN2-GFP and BRI1-GFP internalization.The internalized PIN2 and BRI1 are subsequently transported to the vacuole via the trans-Golgi network/early endosome (TGN/EE) and prevacuolar compartment (PVC) pathways. Intriguingly, salicylic acid (SA) negatively regulates the effect of Pep1 on PM endocytosis. This study sheds light on a previously unknown signaling pathway by which danger peptides like Pep1 influence PM dynamics, contributing to a deeper understanding of the function of plant elicitor peptide.